Studio practices for shaping and heat-setting synthetic fabric - Haar, Sherry J. (My University, 2011)
Heat-setting of synthetic fabrics is an industrial stabilization process that has been adapted by designers to create dimensional textures through shaped-resists and non-industrial heat-setting methods. The article overviews heat-setting properties, physical resist techniques, and presents an experiment to determine best practices for heat-setting physically resisted polyester fabric. Two polyester fabrics, organza and lining, were gathered and secured to a wooden dowel and heat-set under four heating conditions: steaming in a pressure cooker, boiling in a pot of water, dry heat in a conventional oven, and radiation waves in a microwave oven. Pre- and post-treatment lengths were analyzed using GLM for two-way ANOVA and post hoc tests. Based on results from the statistical analysis and visual evaluation, steaming in a pressure cooker is recommended for sheer fabrics such as organza and dry heat from a conventional oven for lining weight fabrics.
Keywords: Thermoplastic; Heat-set; Physical resist; Shibori; Polyester